The use of routine data from primary care practices in Germany to analyze the impact of the outbreak of SARS-CoV-2 on the utilization of primary care services for patients with type 2 diabetes mellitus - Christoph Strumann; Paul-Georg Blickle; Wolfgang C. G. von Meißner; Jost Steinhäuser (BMC Primary Care, 2022)
Abstract Background Routinely collected health data from ambulatory care providers offer a wide range of research opportunities. However, the access is often (e.g., technically) hindered, particularly in Germany. In the following, we describe the development of an infrastructure for the analysis of pseudonymized routine data extracted from primary care practices in Germany. Further, we analyze the impact of the outbreak of SARS-CoV-2 on the utilization of primary care services for patients with type 2 diabetes mellitus (DM type 2). Methods In this retrospective cohort study, routine data were extracted from nine private primary care practices before and since the outbreak of SARS-CoV-2 in Germany. The sample consisted of patients who were treated between 2016 and 2022 in one of the participating practices. The effects of the outbreak on the frequency of practice visits and the disease course of DM type 2 patients were analyzed by means of bivariate and multivariate analyses. Results The developed infrastructure offers an analysis of routine data from outpatient care within 24 h. In total, routine data of 30,734 patients could be processed for the analyses with 4182 (13.6%) patients having a diagnosed DM type 2 and 59.0% of these patients were enrolled in a disease management program (DMP). In the multivariate analysis, there was a significant negative effect of the SARS-CoV-2 outbreak on utilization of outpatient services of patients with DM type 2 disease. This decrease was less pronounced among DMP patients. The glycated haemoglobin level (HbA1c) has not changed significantly. Conclusions The study showed that the analysis of routine data from outpatient care in Germany is possible in a timely manner using a special developed electronic health record system and corresponding software. The significantly negative effect of the SARS-CoV-2 outbreak on utilization of outpatient services of patients with DM type 2 disease was less pronounced among DMP patients. Two years after the start of the Covid pandemic a significantly worsened course of illness cannot be observed. However, it must be taken into account that the observation period for clinically relevant outcomes is still relatively short.